Smart rest pillow with integrated wellness features: promoting better sleep and mental relaxation - Mohd Amiruddin, Ain Nursyafiqa; Mohd Azwan, Nurul Farisya Irwayu; Mohd Taufik, Nurul Najihah; Nik Mohdnizam, Nik Nurul Aisyah; Kamaruddin, Nik Amni Zahirah (Universiti Teknologi MARA, Negeri Sembilan, 2025)
In today’s busy world, many people struggle with getting enough rest, managing stress, or simply finding time to relax. Whether it’s due to work, study, or daily pressures, sleep and self-care often take a back seat. To help with this, our group came up with an innovative concept product called the Smartrest Pillow. This smart pillow is designed to help people relax more easily, sleep better, and feel calmer without needing a bunch of separate gadgets or routines. The Smartrest Pillow combines several soothing features into one familiar and comforting item. It has cooling gel memory foam to keep you comfortable throughout the night, built-in Bluetooth speakers to play calming music or nature sounds, and gentle vibrations that help your body unwind like a light massage. There’s also an optional aromatherapy feature that slowly releases calming scents like lavender or chamomile to help you fall asleep faster. Everything is controlled through a simple app called CalmCloud, where users can adjust settings, track their sleep patterns, and even set reminders for relaxation or self-care. The pillow’s soft bamboo fabric and rechargeable design make it both eco-friendly and easy to use. What makes this pillow special is how it turns something as ordinary as going to bed into a peaceful and personalized experience.Our goal is to make stress relief and mental wellness easier to achieve right from your pillow. By bringing together comfort, smart technology, and relaxation, the Smartrest Pillow encourages better habits and helps people feel more rested, both physically and emotionally.